(untitled) (American Journal of Islam and Society, 2024)
Volume 41 Issue 2 of the American Journal of Islam and Society comprises four main research articles, each of which engages themes of Muslim collectivity, community, and umma from different vantage points. The first article is Rezart Beka’s contribution, “The Reconceptualization of the Umma and Ummatic Actions in Abdullah Bin Bayyah’s Discourse.” The second article is titled “An Egyptian Ethicist: Muḥammad ʿAbd Allāh Drāz (1894-1958) and His Qurʾān-Based Moral Theory” by Ossama Abdelgawwad. The third research article for this issue is “The Other Legitimate Game in Town? Understanding Public Support for the Caliphate in the Islamic World”, a co-authored study by Mujtaba A. Isani, Daniel Silverman, and Joseph J. Kaminski. The fourth and final research article in this issue is Ashwak Hauter’s, “The Reparative Work of the Imagination: Yemen, ‘Afiya, and Politics of the Umma”. This issue of the American Journal of Islam and Society also includes a number of insightful book reviews, including editor Ovamir Anjum’s review essay engaging Joel Hayward’s recent work The Warrior Prophet: Muhammad and War and Celene Ibrahim’s author response to a review authored in a previous issue on her book, Women and Gender in the Qur’an.